Digital Transformation in School Financial Management: Its Role in Enhancing Educational Efficiency - Sofarudin, Dedi; Martiyani, Alfina; Sutrisno (Jurnal Paedagogy, 2026)
This study aims to examine the role of technology-based financial management in improving educational efficiency in public elementary schools. A quantitative approach with a correlational research design was employed. The respondents consisted of 60 school stakeholders, including principals and BOS treasurers from public elementary schools in Brebes Regency, who were selected using purposive sampling based on their direct involvement in school financial management. Data were collected using a structured questionnaire developed based on indicators of financial management (transparency, accountability, budget accuracy, and resource optimization) and educational efficiency. The data were analyzed using descriptive statistics and simple linear regression analysis. The results showed that technology-based financial management had a significant effect on educational efficiency (R² = 0.507, p < 0.05). This finding indicates that 50.7% of the variance in educational efficiency is explained by the implementation of digital financial management systems, while the remaining 49.3% is influenced by other factors, such as digital literacy, infrastructure availability, and leadership commitment. The findings demonstrate that digital financial systems enhance transparency, accountability, and budget accuracy while reducing bureaucratic inefficiencies and minimizing errors in financial reporting. This study implies that Education Offices should strengthen the standardization of digital financial systems and provide continuous training for school financial administrators. Furthermore, improving ICT infrastructure, particularly in rural areas such as Brebes Regency, is essential to support the effective implementation of digital financial governance in schools.